Effect of food additives on the productivity of silk worm Bombyx Mori L. - El-Sayed, Nagda A.; Mesbah, H.A.; El- Seehy, M.A.; EL-Kady, Magda B.A.; El-Gamel, Omaima M.M (2013)
The aim of the present work is to study the effect of supplementing mulberry leaves with two types of honey and palm pollen either alone or mixed at a level of different concentrations on certain biological and reproductive parameters of the mulberry silkworm Bombyx mori L. particularly silk and egg production. The obtained results indicated that the treatment of mulberry leaves with mixture of citrus honey and palm pollen at a level of 5mg + 1gm / 100ml water significantly increased the biological parameters in comparison with that of the control. The treatments of both mixed types of honey bee with palm pollen increased moth's productivity and gave higher values in the egg production.
Includes references.
Summary in Arabic.
1
Keywords: Silkworms -- Feeding and feeds; Honey -- Uses; Silkworms -- Research